Los derechos de los trabajadores y el registro de las actas de finiquito de manera virtual. - Duchi Yuqui, Dennis Francisco (2022)
This settlement certificate is a document that evidences the termination of the employeremployee relations because of the causes established or agreed upon in the certificate. The employer and worker must accept the same and also contains the settlement that the worker must receive. As a consequence of the work carried out for the employer's benefit, these acts are registered virtually in the Single Labor System of the Ministry of Labor Relations. Based on the previous, it is evidenced that if the workers' rights are violated with the registration of the settlement records online. The employer makes the settlement record without control of the Labor Inspectors. They do not take care that the settlement certificate is detailed, nor does it imply the waiver of rights, producing economic damage for workers on certain occasions. The settlement record cancels values lower than those provided by law, and, on other events, cases of untimely dismissal are made invisible with said acts. The proposed objectives, the documentary bibliographic research, and the synthetic, analytical method were used. The standards of International Instruments, the Constitution of the Republic, and the Labor Code that relate to the proposed problem were selected and analyzed. By the researcher. The theoretical framework was also supported by labor law boo.